Comparative evaluation of enzyme-free nanoclay-ionic liquid based electrodes for detection of bioanalytes. Issue 70 (12th July 2016) - Joshi, Nidhi; Sharma, Abhimanyu; Rawat, Kamla; Asokan, K.; Solanki, P. R.; Lakshmi, G. B. V. S.; Kanjilal, D.; Bohidar, H. B.
Abstract : Enzyme-free electrodes were fabricated using mixed nanoclays and ionic liquids. Abstract : Enzyme-free electrodes were fabricated using nanoclay LAPONITE® and montmorillonite (MMT) and imidazolium based ionic liquids (ILs), 1-ethyl-3-methyl imidazolium chloride ([C2mim][Cl]) and 1-methyl-3-octyl imidazolium chloride ([C8mim][Cl]). Here, we have presented a set of quantitative results which conclude that these enzyme-free electrodes can be used successfully for the development of strip-sensors for detection of bioanalytes. Introduction of ILs into nanoclay dispersions resulted in the enhancement of stability of the thin film electrodes formed of the NC-IL materials. The fabricated electrodes were used for sensing various bioanalytes, such as ascorbic acid (AA), oxalic acid (OA), urea (U), citric acid (CA), glucose (Glu) and cholesterol (Chox). The influence of different alkyl chain lengths of ionic liquids, and the aspect ratio of nanoclay platelets were studied with respect to their electrochemical response to different analytes, which covered seven distinct matrices coated on the electrode surface. Further, the effect of oxygen ion beam irradiation on the electrochemical profiles of these electrodes was explored. The irradiation leads to reduction of the electrochemical properties by blocking certain active charge transfer sites. The electrochemical characterization of these electrodes was done using cyclic voltammetry (CV), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM).